2012
DOI: 10.1089/apc.2012.0122
|View full text |Cite
|
Sign up to set email alerts
|

Appearance Concerns and Psychological Distress Among HIV-Infected Individuals with Injection Drug Use Histories: Prospective Analyses

Abstract: Morphologic alterations in body composition are common among HIV-infected individuals, and these changes are associated with increased appearance concerns. Previous cross-sectional data indicate that appearance concerns among HIV-infected individuals are related to increased levels of psychological distress. However, to date, no known prospective data have been published on these relationships. The purpose of the current study was to address the temporal prediction of appearance concerns on depression and anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
13
0
3
Order By: Relevance
“…PLWH may try to gain weight to avoid the social stigma associated with HIV. Appearance concerns are common in PLWH as the illness and/or treatment may affect body changes such as increased fat in the belly, neck, shoulders, breasts, and face (Blashill, Gordon, & Safren, 2012). One participant reported, “I’m not too big but I had like a little pouch.…”
Section: Resultsmentioning
confidence: 99%
“…PLWH may try to gain weight to avoid the social stigma associated with HIV. Appearance concerns are common in PLWH as the illness and/or treatment may affect body changes such as increased fat in the belly, neck, shoulders, breasts, and face (Blashill, Gordon, & Safren, 2012). One participant reported, “I’m not too big but I had like a little pouch.…”
Section: Resultsmentioning
confidence: 99%
“…13 Para M., os valores e padrões de corpo começaram a mudar ao longo da vida. Obesa na adolescência, ser chamada de O uso dos ARVs e a infecção modificaram seu corpo, que se tornou uma vitrine da doença, o que ela tenta esconder pelo medo do preconceito.…”
Section: […] Muita Diferença Depois Que Eu Comecei a Usar O Medicamenunclassified
“…Obesa na adolescência, ser chamada de O uso dos ARVs e a infecção modificaram seu corpo, que se tornou uma vitrine da doença, o que ela tenta esconder pelo medo do preconceito. Estudo realizado por Blashill 13 revela que a PVHA tem sua qualidade de vida ameaçada pela lipodistrofia, sendo que as que são diagnosticadas têm duas vezes mais receio de serem reconhecidas como soropositivas para HIV devido à sua aparência física.…”
Section: […] Muita Diferença Depois Que Eu Comecei a Usar O Medicamenunclassified
See 1 more Smart Citation
“…Unfortunately, the authors analyzed stigma and depression as a single variable, so it is difficult to determine the impact depression alone had on body image, or if stigma affected depression and vice versa. Blashill, Gordon and Safren (2012), studied a mixed gender sample of 89 PL WHA with opioid-dependence, and found that concerns about physical appearance were associated with increased depression and anxiety. Unfortunately, neither of these studies stratified the results by gender, however, they were included in this project because of the consistency in the relationship between body image and depression.…”
Section: Factors Correlated With Comorbid Depressionmentioning
confidence: 99%